Contribuição do gradiente longitudinal e dos tributários na estruturação da comunidade zooplanctônica nos reservatórios em cascata no rio Tocantins - Mendonça, Laura Beatriz Gomes (2022)
Understanding the importance of the dispersion of planktonic organisms in the structure of communities has been one of the main goals of ecological studies in the stretches of rivers affected by the construction of reservoirs. Along a cascade of reservoir, the diversity of planktonic organisms located in the central body of a reservoir can be influenced both by the tributaries that flow into this reservoir and by the reservoirs upstream. In this way, the main goal of this study was to analyze the structure of the zooplankton community along a cascade of reservoirs in the Tocantins River and verifying the importance of tributaries and upstream reservoirs in the composition and abundance of species. We analyzed the richness and abundance of the zooplankton community in a stretch of the Tocantins River composed of three reservoirs built in cascade: HPP Cana Brava, São Salvador and Peixe Angical. The study was carried out at 20 sampling points in different seasonal periods. We performed a beta diversity analysis between the tributaries and the central body of the reservoirs, between the points located only on the central body of the three reservoirs and between the tributaries, to verify the similarity in the structure of the communities between the different regions. The highest beta diversity, in other words, the lowest similarity in the structure of zooplanktonic communities, was obtained between the sampling points located in the tributaries and in the central body of each of the studied reservoirs, mainly the rainy season, demonstrating the influence of seasonality. The abiotic factors were also different when comparing the dry and rainy periods, especially in the tributaries. The lowest values of beta diversity were measured comparing the central body of the reservoirs, mainly for rotifers and microcrustaceans. This result demonstrates the importance of the longitudinal dispersion of these groups among the reservoirs. Besides, considering the low richness of exclusive taxa inside the reservoirs (in the central body), we can infer that the dispersion of taxa from the tributaries to the central body is important, and the population size of some species will be favored under the lentic conditions of the reservoirs, changing the structure of communities. This study contributes to a better understanding of the factors responsible for the diversity of zooplanktonic community in reservoirs, considering the abiotic component, the importance of longitudinal and lateral (tributary) dispersion of the different zooplanktonic groups and the seasonal component.